ANALISIS KUALITAS PELAYANAN DEPARTEMEN FOOD AND BEVERAGE SERVICE DI PADMA HOTEL BANDUNG - Muhammad Dafa Sukmajaya; Siti Zakiah (LPSDI Bina Patria, 2024)
The city of Bandung is one of the cities in Indonesia that attracts many tourists, so many hotels are established close to the tourism industry. Padma Hotel Bandung is an example of a hotel in the city of Bandung and is included in the five star hotel category. This research was conducted to analyze the quality of service provided by the Food and Beverage Department at Padma Hotel Bandung, analyze the attributes that guests consider important and unimportant, and to develop strategies to improve the quality of service at the hotel. The data collection technique was carried out by collecting questionnaires and analyzing them using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The research results show that guests are very satisfied with the quality of service provided by Padma Hotel Bandung as evidenced by the CSI value of 90.62. Further analysis using the IPA method produces four quadrants where quadrant one is filled with one attribute that needs to be improved because its performance is lacking and is considered important, and there are 6 attributes in quadrant two that are considered important and have received satisfaction from guests. Other attributes in quadrants three and four are attributes that according to guests are not too important so they can be put aside first. This research can be an illustration and consideration for Padma Hotel Bandung to maintain its quality and existence